Drug Utilization and Evaluation of Antiepileptic Drugs in a Tertiary Care Hospital - SK, Arifa Begum; Durga, Ch Vaishnavi; Sahithi, B; Leema, K; Vaishnavi, K; Swathi, R P; Swathi, B; Rajendra, V; Begum, Shaheen (Journal of Pharmacy Practice and Community Medicine)
Aim: Drug utilization and evaluation (DUE) study of antiepileptic drugs in a tertiary care hospital. Methods: A total of 110 case records of patients were included in a prospective observational study which was conducted for duration of 6 months. The prescription pattern was analyzed based on age, gender, route of administration, indication, duration of therapy, type of seizures, generation of Anti-Epileptic Drugs (AEDs), and rationality. Results: AEDs were prescribed more for patients between the ages of 51-60 years. The majority of patients receiving AEDs were males and AEDs were mostly used in the neurology department followed by neurosurgery and general medicine. Levetiracetam was prescribed most commonly as monotherapy. Lorazepam and midazolam were the most common add-on drugs. Gabapentin was mostly prescribed for severe neuropathic pain. The oral route was the common route of administration of AEDs. AEDs were highly prescribed for prophylaxis of seizures. Second-generation AEDs were highly used compared to other drugs. Conclusion: Second-generation AEDs were used as monotherapy and were found to be effective in reducing seizures and economically affordable for patients. As monotherapy, levetiracetam was the drug of choice followed by lorazepam.
Keywords: Drug Utilization Evaluation (DUE); Epilepsy; Antiepileptic drugs; Levetiracetam; Phenytoin; Seizures